2014
DOI: 10.1111/ejh.12317
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term follow‐up of bone density, general and reproductive health in female survivors after treatment for haematological malignancies

Abstract: The purpose of this study was to assess the ovarian function, fertility and bone mineral density in women who previously had treatment for different haematological malignancies (HMs). The overall survival and cure rates of patients with HMs have improved dramatically. The treatment affects fertility and bone density. Fifty-two premenopausal women, from Stockholm region, were included in the study between 1998 and 2002, followed until 2011. The diagnoses were acute lymphoblastic leukaemia (n = 6), acute myeloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…After review of the titles and abstracts, 41 studies were identified as potentially eligible for inclusion. After full review, four systematic reviews were excluded (Levine et al, 2015;Lopategui et al, 2017;van Dorp et al, 2016;Burkart et al, 2019), one publication because data could not be extracted (Zynda et al, 2012), 15 original studies because of the absence of a healthy control group (Carter et al, 2006;Kiserud et al, 2007;Sudour et al, 2010;Speiser et al, 2011;Hamre et al, 2012;Hansen et al, 2013;Reinmuth et al, 2013;Shepherd et al, 2006;Greaves et al, 2014;Naessén et al, 2014;Hoshi et al, 2015;Wu et al, 2015;Yonemoto et al, 2016;Shandley et al, 2017;Nichols et al, 2018) and three additional studies because they generically referred to reproductive prognosis after cancer without splitting data for cancer subtypes (Green et al, 2009;Reulen et al, 2009;Dillon et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…After review of the titles and abstracts, 41 studies were identified as potentially eligible for inclusion. After full review, four systematic reviews were excluded (Levine et al, 2015;Lopategui et al, 2017;van Dorp et al, 2016;Burkart et al, 2019), one publication because data could not be extracted (Zynda et al, 2012), 15 original studies because of the absence of a healthy control group (Carter et al, 2006;Kiserud et al, 2007;Sudour et al, 2010;Speiser et al, 2011;Hamre et al, 2012;Hansen et al, 2013;Reinmuth et al, 2013;Shepherd et al, 2006;Greaves et al, 2014;Naessén et al, 2014;Hoshi et al, 2015;Wu et al, 2015;Yonemoto et al, 2016;Shandley et al, 2017;Nichols et al, 2018) and three additional studies because they generically referred to reproductive prognosis after cancer without splitting data for cancer subtypes (Green et al, 2009;Reulen et al, 2009;Dillon et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Patients with leukemia are at high risk for transfer of malignant cells with the transplanted tissue (21). Yet early age at diagnosis and high ovarian failure rates after treatment put them at a high need for OTCP (22,23), especially as immediate chemotherapy is required on admission, precluding the use of other fertility preservation techniques (14). To provide maximal safety and avoid reintroduction of malignancy on transplantation, both postchemotherapy tissue harvesting and an intense search for leukemic cells were performed.…”
Section: Eligibility and Indications For Otcp And Transplantationmentioning
confidence: 99%
“…Neither of them were treated with chemotherapy before tissue collection. The use of the described approach significantly increases transplantation safety, potentially overcoming previous restrictions for transplantation (22,23).…”
Section: Eligibility and Indications For Otcp And Transplantationmentioning
confidence: 99%
“…Firstly, this special and growing population have mixed health problems, habitually underwent multiple and different chemotherapy protocols (including myeloablative conditioning) and/or radiation treatment schedules (including TBI) previously to SCT, that might lead to decreased gonadal function and fertility, which is one of the most important factors in determining reduced BMD in these patients [40,58]. Secondly, after SCT these patients receive immunosuppressive regimens with glucocorticoids, and they might develop several complications, including graft-versus-host disease (GVHD), which requires additional long-term excessive dose of glucocorticoids, and consequently aggravate bone loss and the risk for AVN [58,59].…”
Section: Survivors Of Hematopoietic Stem Cell Transplantation: a Specmentioning
confidence: 99%